Cold Drink Attenuates Heat Strain during Work-rest Cycles - Lee, J.K. W.; Yeo, Z. W.; Nio, A.Q. X.; Koh, A.C. H.; Teo, Y. S.; Goh, L. F.; Tan, P.M. S.; Byrne, C. (International Journal of Sports Medicine, 2013)
There is limited information on the ingestion of cold drinks after exercise. We investigated the thermoregulatory effects of ingesting drinks at 4°C (COLD) or 28°C (WARM) during work-rest cycles in the heat. On 2 separate occasions, 8 healthy males walked on the treadmill for 2 cycles (45 min work; 15 min rest) at 5.5 km/h with 7.5% gradient. Two aliquots of 400 mL of plain water at either 4°C or 28°C were consumed during each rest period. Rectal temperature (Tre), skin temperature (Tsk), heart rate and subjective ratings were measured. Mean decrease in Tre at the end of the final work-rest cycle was greater after the ingestion of COLD drinks (0.5±0.2°C) than WARM drinks (0.3±0.2°C; P<0.05). Rate of decrease in Tsk was greater after ingestion of COLD drinks during the first rest period (P<0.01). Mean heart rate was lower after ingesting COLD drinks (P<0.05). Ratings of thermal sensation were lower during the second rest phase after ingestion of COLD drinks (P<0.05). The ingestion of COLD drinks after exercise resulted in a lesser than expected reduction of Tre. Nevertheless, the reduction in Tre implies a potential for improved work tolerance during military and occupational settings in the heat.
Keywords: thermoregulation; internal cooling; military